Implementasi Parenting Berkelanjutan TK Aisyiyah I, II, III dan IV Rawalo Kec. Rawalo, Kabupaten Banyumas - Tatik Aryanti; Melati Ismi Hapsari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
Children are small people who have the potential to be developed. Children have certain characteristics that are unique and not the same as adults, they are always active, dynamic, enthusiastic and curiosity about what they see, hear, feel, as thought they never stop exploring and learning. The age of birth to enter the basic education is a golden period as well as a critical period in the life stage that will determine the development of the next child. This period is a good time to lay the groundwork for the development of physical, linguistic, social emotional, self concept, art, moral and religious value. Parenting progam aims to give provision and understanding the parents about nurture which give stimulation for childhood. This nurture will support childhood in education activity in PAUD Aisyiyah (Aisyiyah Kindergarten). The benefit for parents and society, can give understanding about childhoodeducation and sensitize parents about the important of early stimulation for child in daily nurture. For childhood, with environtmental conditions which condicive to development and growth from fmily and PAUD (Kindergrten) achieving success and development task. Children with special needs can be interpreted with children who are classified as disabled or who bear the disabilities and also potential and talented children. Children with special needs are those with temporary or permanent special needs that require more intense educational services. Needs may be caused by abnormalities or are indeed innate or due to distressing economic, political, social, emotional and behavioral pressures. Called special needs because children have abnormalities and presence with normal children in general. Having a healthy, active, and intelligent child would be the the dream off all parents. But, not a few parents of children with special needs who feel the dream is destroyed. To as children with abnormal growth because they have some diferrences with normal children. Children with special needs are usually referred Accepting reality is the key to the first handling of children with special needs and by giving love adn more attention. Through appropriate therapy and approprite education, children with special needs are able to get a relatively more normal life. Keywords : Sustainable parenting,children with special need